In the shadow of Chang’an: the space transformation of villages within a cultural heritage site - Ji, Jiahui (2023)
Excluded from heritage recognition but in the proximity of cultural heritage, the villages within a Cultural Heritage Site (CHS), after being influenced by long-term restrictive conservation policies for protecting the heritage integrity, have gained more freedom than was allowed before and become a space involving multifaced stakeholders to alleviate the tension between cultural heritage conservation and village development. As a result, the villages within a CHS have been faced with much more complex situations as more stakeholders participate in and invoke the profound space transformation here. The perceptions of villages within a CHS can become polarised around a number of positions: the local government controls the administrative power on the management of villages by coordinating the utilization of cultural resources and the conservation of cultural heritage integrity; the capital demands the maximum economic benefits; and the local people’s complex and immediate interests related to the everyday life. All of these positions entangle and compete with each other, leading to increasingly intense conflicts and pushing the villages within a CHS into a more complex state.